2022
DOI: 10.1177/23969415221091928
|View full text |Cite
|
Sign up to set email alerts
|

Repeating purposefully: Empowering educators with functional communication models of echolalia in Autism

Abstract: Background and Aims Echolalia, the repetition of speech, is highly prevalent in school aged children with Autism. Prior research has found that individuals with echolalia use their repetitions to engage in communicatively functional speech, in the absence of self-generated speech. Educators are the natural audience for a wide vary of echoed utterances across environments and in differing contexts. The objectives of this paper were three-fold: (1) to systematically investigate how researchers identify and ascri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…For example, this study did not include a communication therapist, as did Breiting and Maas (2021). Nor did this study include teachers, as did Cohn, McVilly, Harrison, and Stiegler (2022). Third, Rossignol and Frye (2021) assessed the utility of vitamin B12, but the current study did not assess any of the five youth Verbal/non-verbal expressive receptive communication 24 for the presence (or absence) of vitamin B12.…”
Section: Limitationsmentioning
confidence: 95%
“…For example, this study did not include a communication therapist, as did Breiting and Maas (2021). Nor did this study include teachers, as did Cohn, McVilly, Harrison, and Stiegler (2022). Third, Rossignol and Frye (2021) assessed the utility of vitamin B12, but the current study did not assess any of the five youth Verbal/non-verbal expressive receptive communication 24 for the presence (or absence) of vitamin B12.…”
Section: Limitationsmentioning
confidence: 95%
“…A recent review suggested functions of echolalia have been investigated via multiple methodologies, including looking at surface structure of the repetition, relying on the communicative partner for determining function, evaluating the interaction in the context of the surrounding environment, or evaluating alterations of speech prosody (e.g., tone, volume, inflections, rhythm) as indices of function ( Cohn et al, 2022 ). Although newer conceptualizations consider echolalia as occurring within a communicative context, this was not always how echolalia was conceptualized ( Cohn et al, 2022 ). Early research suggested that presence of echolalia was “auto-erotic and auto-aggressive” ( Buium & Stuecher, 1974 , p. 353).…”
Section: Presentations Of Echolaliamentioning
confidence: 99%
“…During the behaviorism movement, echolalia was reclassified as a self-stimulatory behavior ( Gernsbacher et al, 2016 ). Echolalia has also been described as a lack of inhibitory control, such as the case in GTS ( Ganos et al, 2012 ), and can have some non-communicative functions ( Cohn et al, 2022 ). However, recent evidence suggests that echolalia may have more of an adaptive function instead of being the result of a maladaptive neural function or deficit.…”
Section: Presentations Of Echolaliamentioning
confidence: 99%
See 2 more Smart Citations